Somatotipo como indicador de desempenho em atletas de futsal feminino - Queiroga, Marcos Roberto [UNESP]; Ferreira, Sandra Aires [UNESP]; Pereira, Gleber [UNESP]; Kokubun, Eduardo [UNESP] (FapUNIFESP (SciELO), 2008)
The present study aimed to verify whether body somatotype was indicative of competitive success in female futsal (indoor soccer) players. One hundred and twelve players (22.1 ± 5.4 years; 58.4 ± 6.9 kg; 161.8 ± 6.2 cm), from ten teams and seven different states, had participated in a national competition. The anthropometric date was analyzed using one-way ANOVA for repeated measures. The somatotype dispersion distance was applied to compare somatotypes between the champion team (reference) and the other teams (from 2nd to 10th position). Anthropometric characteristics did not differ significantly among teams. The results showed that the endomorphic component was predominant in relation to the mesomorphic and ectomorphic component, irrespective of a team's ranking at the end of the competition. Therefore, the body somatotypes of female futsal teams cannot be considered as indicative of their competitive success.
Somatotype and performance in female futsal players
Keywords: Anthropometry; Female soccer; Somatotype dispersion distance